Digitalization and internationalization of SMEs: A Systematic Literature Review - Umu Rosyidah; Sudarmiatin Sudarmiatin; Hadi Sumarsono (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The objective of this study is to evaluate the prevailing trends in publications and investigate the literature derived from multiple studies concerning the impact of digitalization on SMEs and their internationalization process.Method — We employ the Systematic Literature Review (SLR) methodology to identify and consolidate publication trends from various articles. The literature utilized in this study is sourced from the Scopus database. By referring to the PRISMA chart, a total of 33 literature works were selected for analysis using VOSviewer. In this research, we utilize bibliometric analysis to examine article trends and employ content analysis to assess the literature.Result — We discovered that there were 19 keywords representing the latest and seldom explored themes among researchers, which were organized into 5 clusters for further analysis within a research framework. Moreover, we identified new and infrequently studied themes such as effectuation, international performance, digital transformation, digital technologies, and export performance. Additionally, we uncovered novel research topics that have the potential to inspire future studies in related areas.Contribution — This study contributes by examining literature on digitalization and internationalization, identifying research trends and proposing future directions, especially for SMEs in Southeast Asian countries. It also introduces the rarely-used Systematic Literature Review (SLR) approach to examine the role of digitalization in internationalization, challenging the dominance of quantitative methods in prior research.